Histological aspects of the renal sexual segment of Brazilian snakes of the Boidae family - Bento, Heitor José; Ferreira, Adelina; Rosa, Janaina Marcela Assunção; Campos, Camila Gonçalves; Silva, Sávio Lucas Rodrigues; Curcio, Felipe Franco; Pescador, Caroline Argenta; Paz, Regina Celia Rodrigues (Anatomia, histologia, embryologia, 2024)
Snakes represent a wide and diverse group of species and have anatomical particularities, such as the renal sexual segment (RSS), a structure located in the kidneys and formed from the hypertrophy of the urinary ducts and nephrons. This study aims at describing the histological aspects of the RSS of Boa constrictor, Epicrates cenchria and Corallus hortulanus, all of which are Brazilian snake species from the Boidae family. The reproductive system and kidneys of five male specimens of E. cenchria, three male specimens of C. hortulanus and two male specimens of B. constrictor were obtained. Tissue samples were processed histologically and different stains used (Toluidine Blue, Alcian Blue and Periodic Acid Schiff). The histological evaluation of the RSS of E. cenchria, C. hortulanus and B. constrictor shows that the RSS in these species varies when comparing individuals in the reproductive period with those which are not. It also allows for the observation of the segment's secretory activity in animals in the reproductive stage (mature sperm in the lumen of the seminiferous tubules) as well as in those which are not. Finally, the histological evaluation also reveals the variation of the secretion product in individuals in the reproductive period, in those which are not, and also among individuals within the same reproductive stage.